Impact of Comic-Based Learning Media Using StoryboardThat on Enhancing Student Academic Performance - Rochmat, Cecep Sobar; Amanah, Khusnul (Universitas Muhammadiyah Magelang, 2025)
This research examines how the use of learning media influences students' academic performance. A quasi-experimental design utilizing a quantitative approach was applied. The study utilized the Nonequivalent Control Group Design. The study involved two groups: an experimental class that utilized comic media created with Storyboard That, and a control class that followed traditional teaching methods for comparison. The study utilized a reliable and validated achievement test, administered as both a pretest and a posttest. The findings demonstrated a notable disparity in the learning outcomes between students in the experimental group and those in the control group, supported by a significance value (Sig. 2-tailed) of 0.023 ≤ 0.05. The average learning score in the experimental class increased significantly from 34.60 to 84.25, while the control class's average rose from 37.39 to 74.72. These findings demonstrate that the application of comic-based learning media using Storyboard That positively influences the improvement of students' learning outcomes.